Classification of prestrike types in vacuum interrupter eroded by inrush current based on DC dynamic gap measurement method. - Pu Chen; Yun Geng; Jing Yan; Hannan Shan; Yan Wang; Zhiyuan Liu; Hanyan Xiao; Tianxin Zhuang (PLoS ONE, 2025)
The characteristics and types of prestrike are critical factors affecting the performance of vacuum circuit breakers (VCBs) in controlled switching. However, there is a lack of studies on the prestrike characteristics and types in vacuum interrupter (VI) after inrush current erosion. This paper investigates the prestrike characteristics and types in VI after inrush current erosion, using a novel method for measuring field emission current under DC voltage. Through experiments, the prestrike characteristics after inrush current erosion were obtained, including prestrike dispersion and prestrike gap. Furthermore, based on the prestrike gap and field emission current, the prestrike types observed in the experiments were classified into three categories: field emission induced prestrike (FEPS), particle-induced prestrike (PPS) and field emission-particle induced prestrike (FE-PPS). The average prestrike gap for these three types were 1.525 mm, 3.809 mm, and 2.887 mm, respectively. PPS showed no significant field emission current, while the field emission current at prestrike moment for FE-PPS was approximately 48.89% of that observed in FEPS. These findings have important implications for the development of controlled switching technology in VCB.